Anti-hypertensive drugs and skin cancer risk: a review of the literature and meta-analysis. (February 2018) - Gandini, Sara; Palli, Domenico; Spadola, Giuseppe; Bendinelli, Benedetta; Cocorocchio, Emilia; Stanganelli, Ignazio; Miligi, Lucia; Masala, Giovanna; Caini, Saverio
Highlights: Long-term users of photosensitizing drugs might be at increased skin cancer risk. We reviewed studies focusing on skin cancer risk among anti-hypertensives users. We included and meta-analysed nineteen independent observational studies. Calcium channel blockers users were at increased skin cancer risk. β-blockers users were at increased risk of developing cutaneous melanoma. Abstract: Introduction: Several anti-hypertensive drugs have photosensitizing properties, however it remains unclear whether long-term users of these drugs are also at increased risk of skin malignancies. We conducted a literature review and meta-analysis on the association between use of anti-hypertensive drugs and the risk of cutaneous melanoma and non-melanoma skin cancer (NMSC). Methods: We searched PubMed, EMBASE, Google Scholar and the Cochrane Library, and included observational and experimental epidemiological studies published until February 28th, 2017. We calculated summary relative risk (SRR) and 95% confidence intervals (95% CI) through random effect models to estimate the risk of skin malignancies among users of the following classes of anti-hypertensive drugs: thiazide diuretics, angiotensin converting enzyme inhibitors (ACEi), angiotensin receptor blockers (ARB), calcium channel blockers (CCB) and β-blockers. We conducted sub-group and sensitivity analysis to explore causes of between-studies heterogeneity, and assessed publication bias using a funnel-plot based approach. Results: Nineteen independent studies were included in the meta-analysis. CCB users were at increased skin cancer risk (SRR 1.14, 95% CI 1.07–1.21), and β-blockers users were at increased risk of developing cutaneous melanoma (SRR 1.21, 95% CI 1.05–1.40), with acceptable between-studies heterogeneity (I 2 < 50%). There was no association between thiazide diuretics, ACEi or ARB use and skin cancer risk. We found no evidence of publication bias affecting the results. Conclusion: Family doctors and clinicians should inform their patients about the increased risk of skin cancer associated with the use of CCB and β-blockers and instruct them to perform periodic skin self-examination. Further studies are warranted to elucidate the observed associations.